2016
DOI: 10.1097/brs.0000000000001824
|View full text |Cite
|
Sign up to set email alerts
|

When Less Is More

Abstract: Study Design Systematic review. Objective The aim of this study was to review the techniques, indications, and outcomes of minimally invasive surgery (MIS) and separation surgery with subsequent radiosurgery in the treatment of patients with metastatic spine disease. Summary of Background Data The utilization of MIS techniques in patients with spine metastases is a growing area within spinal oncology. Separation surgery represents a novel paradigm where radiosurgery provides long-term control after tumor i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(19 citation statements)
references
References 71 publications
0
16
0
Order By: Relevance
“…Studies comparing minimally invasive surgery and open surgery showed that minimally invasive surgery provided equivalent or superior outcomes with reduced surgical morbidity and complications in spinal metastasis patients [ 70 - 72 ]. However, because the quality of evidence is deemed low in the current literature, no definite conclusion regarding the superiority of minimally invasive surgery over open surgery can be derived, and no strong recommendations have been made at this point [ 73 ].…”
Section: Surgery For Metastatic Spinal Tumorsmentioning
confidence: 99%
“…Studies comparing minimally invasive surgery and open surgery showed that minimally invasive surgery provided equivalent or superior outcomes with reduced surgical morbidity and complications in spinal metastasis patients [ 70 - 72 ]. However, because the quality of evidence is deemed low in the current literature, no definite conclusion regarding the superiority of minimally invasive surgery over open surgery can be derived, and no strong recommendations have been made at this point [ 73 ].…”
Section: Surgery For Metastatic Spinal Tumorsmentioning
confidence: 99%
“…Use of minimally invasive surgical techniques, such as percutaneous stabilisation, use of tubular retractors and mini-open approaches as well as percutaneous cement augmentation of pathological, stable but painful vertebral body fractures, are strongly advised to reduce the peri-operative complication rate. 73 The last element of the NOMS framework is the systemic assessment which means the prediction of the patient’s ability to tolerate the proposed intervention. Comorbidities, general health status and tumour burden have to be assessed.…”
Section: Spinal Metastasesmentioning
confidence: 99%
“…Therefore, the minimally invasive separation of the tumour tissue from the dural sac (separation surgery) with post-operative SRS radiotherapy would be the optimal treatment choice in a high number of cases, providing safe and effective local control. 73 …”
Section: Spinal Metastasesmentioning
confidence: 99%
“…Differently from open surgical treatments, MISS allows earlier post-surgical irradiation (i.e., 1 week after), with patients anecdotally treated as early as 3 days after surgery using a stereotactic technique (94). The efficacy of a combination of MISS and stereotactic body radiotherapy has been adopted also in patients with malignant primary tumors of the spine, for whom en bloc resection was not considered because of the encasement of the spinal cord or vascular structures (95).…”
Section: A New Model: Minimally Invasive Surgery Plus Radiosurgerymentioning
confidence: 99%